Design Of A Waste-Free Power Plant Using A Thermoelectric Generator As A Supply Source For Lamps - Tampubolon, Clarissa Eldora; Cahyadi, Catra Indra; Nur, Fauziah (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
Waste management poses a significant environmental challenge in Indonesia. Ineffective waste handling can lead to various negative environmental impacts. Meanwhile, energy demand continues to rise in line with population growth. One innovative solution to address these issues is the use of Thermoelectric Generator (TEG) technology in a Waste-to-Energy Power Plant (PLTSa) system. This study aims to design and develop a power generation system that utilizes heat energy from the combustion of waste—specifically plastic and paper—to generate electricity, which is then used as a power source for lighting systems. This research uses a quantitative descriptive method to explain a phenomenon or process without relating it to other variables. The energy conversion process is carried out using six TEG modules connected in series to maximize voltage output. The generated voltage is then regulated and stored in a battery using a Solar Charge Controller (SCC), and monitored through an INA219 sensor and an Arduino UNO microcontroller. The system is also equipped with a photocell sensor that enables the light to operate automatically based on the ambient light intensity. Test results show that a temperature difference (∆T) of 227.7°C between the hot and cold sides of the TEG can produce a maximum voltage of 15.87 Volts. The monitoring and automatic control system functions effectively in tracking the TEG output and switching the light on or off according to environmental lighting conditions. Therefore, this system presents a viable alternative solution for renewable energy generation based on waste management.